Acute myeloid leukaemia (FAB AML‐M4Eo) with cryptic insertion of cbfb resulting in cbfb‐Myh11 fusion. Issue 3 (2nd November 2015) - Douet‐Guilbert, Nathalie; Chauveau, Aurelie; Gueganic, Nadia; Guillerm, Gaëlle; Tous, Corine; Le Bris, Marie‐Josee; Basinko, Audrey; Morel, Frederic; Ugo, Valerie; De Braekeleer, Marc
Abstract: Inv(16)(p13q22) and t(16;16)(p13;q22) are cytogenetic hallmarks of acute myelomonoblastic leukaemia, most of them associated with abnormal bone marrow eosinophils [acute myeloid leukaemia French–American–British classification M4 with eosinophilia (FAB AML‐M4Eo)] and a relatively favourable clinical course. They generate a 5′ CBFB‐ 3′ MYH11 fusion gene. However, in a few cases, although RT‐PCR identified a CBFB‐MYH11 transcript, normal karyotype and/or fluorescent in situ hybridization (FISH) analyses using commercially available probes are found. We identified a 32‐year‐old woman with AML‐M4Eo and normal karyotype and FISH results. Using two libraries of Bacterial Artificial Chromosome clones on 16p13 and 16q22, FISH analyses identified an insertion of 16q22 material in band 16p13, generating a CBFB‐MYH11 type A transcript. Although very rare, insertions should be searched for in patients with discordant cytological and cytogenetic features because of the therapeutic consequences. Copyright © 2015 John Wiley & Sons, Ltd.